Emergence of Yalom's Therapeutic Factors in a Peer-Led, Asynchronous, Online Support Group for Family Caregivers. (1st January 2014) - Diefenbeck, Cynthia A.; Klemm, Paula R.; Hayes, Evelyn R.
<x xml:space="preserve">Abstract</x> Support groups fill a critical void in the health care system, harnessing the power of shared experiences to provide support to group members. Likewise, family caregivers fill a void in the health care system, providing billions in unpaid care to the chronically ill. Caregiver support groups offer an opportunity for alleviating the psychological burden of caregiving. The power of any group, including a support group, to foster psychological well-being lies in its ability to cultivate Yalom's therapeutic factors. Gaps in the literature remain regarding the ability of non-prototypical groups to promote therapeutic mechanisms of change. The purpose of this study was to determine if and when Yalom's therapeutic group factors emerged in a peer-led support group delivered in an asynchronous, online format. Qualitative content analysis utilizing deductive category application was employed. Participants' responses were coded and frequency counts were conducted. Results revealed that 9 of 11 therapeutic factors emerged over the course of the group, with Group Cohesiveness, Catharsis, Imparting of Information, and Universality occurring most often. Several factors, including Interpersonal Learning, Corrective Recapitulation of the Primary Family Group, Imitative Behavior, and Development of Socializing Techniques were absent or virtually absent, likely due to the peer-led format of the group. Progression of therapeutic factors over the course of the group is presented. Findings demonstrate the presence of a variety of Yalom's therapeutic factors in an asynchronous, peer-led online support group.